Predictive Factors Influencing the Outcomes of Double “J” Stent Placement in Stage IIIB Cervical Cancer Patients With Hydronephrosis Complication - Dinatha, Gusti Ngurah Krisna; Oka, Anak Agung Gede; Santosa, Kadek Budi (JBN (Jurnal Bedah Nasional), 2022)
Objective: To determine the predictive factors that influence the outcome of Double “J” (DJ) stent placement in stage IIIB cervical cancer patients with hydronephrosis complications. Methods: An analytical observational study with a historical cohort was performed. Patients included in this study was patient with stage IIIB cervical cancer with hydronephrosis complication at Sanglah hospital. We analyzed the influence of time range since diagnosis until DJ stent placement, degree of hydronephrosis, and glomerular filtration rate on the outcomes of DJ stent placement namely: Lower urinary tract symptoms (LUTS), quality of life (QoL), and glomerular filtration rate changes (GFR). Data were tabulated and statistically analyzed using SPSS 25. Results: Of the 44 samples, the mean age of the patients was 51,93 (±7.672) years. Late DJ stent placement increase the risk of severe LUTS (RR: 3.103; 95%CI: 1.319-7.301; p<0.001) compared to patients with early DJ stent placement. We also found that a low glomerular filtration rate (bad renal function) is significantly associated with worse quality of life (RR: 1.917; 95%CI: 1.296-2.835; p<0.001). Conclusion: Delayed DJ stent placement is associated with severe LUTS symptoms, and poor renal function resulted in a poor quality of life.